2012
DOI: 10.1007/s00103-012-1485-4
|View full text |Cite
|
Sign up to set email alerts
|

Die zwei deutschen Geburtskohorten GINIplus und LISAplus

Abstract: Numerous chronic diseases in childhood and adulthood have their origins in perinatal life and are potentially influenced by trans-generational epigenetic processes. Therefore, prospective birth cohorts can substantially contribute to our knowledge about the etiology of diseases including modifiable risk factors. The two population-based German birth cohorts GINIplus and LISAplus aim to describe the natural course of chronic diseases and intermediate phenotypes in childhood and its determinants, and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 64 publications
1
18
1
1
Order By: Relevance
“…For instance, approximately 10 years from the start of the study, the coverage rates in the Ulm SPATZ and Odense Child studies were roughly 20%, while the Generation R study had a higher coverage rate of 43%‐48% . The comparisons of responders and non‐responders also confirmed the general bias towards participants with higher socio‐economic status observed in most of follow‐up studies …”
Section: Commentsupporting
confidence: 54%
“…For instance, approximately 10 years from the start of the study, the coverage rates in the Ulm SPATZ and Odense Child studies were roughly 20%, while the Generation R study had a higher coverage rate of 43%‐48% . The comparisons of responders and non‐responders also confirmed the general bias towards participants with higher socio‐economic status observed in most of follow‐up studies …”
Section: Commentsupporting
confidence: 54%
“…The cohort and recruitment of the participants has been described in detail previously [22][24]. In brief, GINIplus is a longitudinal study of a German birth cohort born between September 1995 and June 1998 in the cities of Munich (urban, south-east of Germany) and Wesel (rural, north-west of Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Using accelerometers and activity diaries in a German cohort of adolescents (GINIplus, [22][24]), the aim of the present study was twofold: First, to introduce a comprehensive approach based on recent recommendations and provide detailed information about cleaning of recorded accelerometry data and handling of information derived from an activity diary applied in German adolescents. Second, to provide first results on objectively measured PA in German adolescents and to give an overview of the information derived from the activity diary.…”
Section: Introductionmentioning
confidence: 99%
“…Several German cohort studies have already shown high enrolment and follow-up rates. This might be due to the fact that the German population, especially in East Germany, is apparently more compliant with the participation in research projects in comparison with other countries [5,11]. People who voluntarily contact the study centre for participation tend to be different from other people in terms of basic demographic factors (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…This implies that cohort studies will always reflect relatively contemporary exposures and practices. However, many ongoing birth cohorts began recruitment in the last century [1,3,5]. Ethnicity, different political and cultural backgrounds are associated with differences in disease prevalence.…”
Section: Introductionmentioning
confidence: 99%